Back‐Illuminated Si‐Based Photoanode with Nickel Cobalt Oxide Catalytic Protection Layer. Issue 10 (28th January 2016) - Bae, Dowon; Mei, Bastian; Frydendal, Rasmus; Pedersen, Thomas; Seger, Brian; Hansen, Ole; Vesborg, Peter C. K.; Chorkendorff, Ib
Abstract: Si is an excellent photo‐absorber for use in dual‐band‐gap photoelectrochemical water splitting. We investigate photoanodes with n + pp + ‐Si configuration under back‐side illumination, which is suited to work in a tandem device stack. A co‐sputtered NiCoO x film coupled to the Si was used as a protective catalyst for the water oxidation reaction in 1 m KOH. The sample showed a high photocurrent (21 mA cm −2 ) under red‐light illumination (38.6 mW cm −2 ). Long‐term stability testing showed a gradual decrease of activity in the beginning, and then the activity increased, yielding a cathodic shift of the onset voltage (>50 mV), likely owing to the divergent response of Ni and Co to the Fe present in KOH. Once the activity of the sample stabilized, no further degradation was observed for the following 6 days, indicating that the demonstrated back‐illuminated photoanode configuration can be considered a promising architecture for use as a bottom cell of the tandem water‐splitting device under alkaline conditions. Abstract : Watch your back : Crystalline Si (c‐Si) coupled with a thin layer of NiCoO x is applied as a photoanode for water oxidation under back‐side illumination to be used as a bottom cell of the tandem water‐splitting device. The thin layer of NiCoO x effectively protects c‐Si from the alkaline electrolyte for 6 days during the oxygen evolution reaction.